2010
DOI: 10.1111/j.1365-2133.2010.10085.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and respective potencies of botulinum toxin A and B: a randomized, double-blind study

Abstract: These results have important implications in clinical routine, especially for autonomic indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
2
16
0
2
Order By: Relevance
“…NeuroBloc and the type A toxins had a similar anhidrotic effect, but the effect of NeuroBloc seemed to diminish more prominently at measurement week 12. This is in accordance with previous clinical studies (15,16). Moreover, the study confirms previous observations of NeuroBloc as an autonomic and sudomotor neurone-specific agent with comparatively poor effect on muscles (12,15,17).…”
Section: Discussionsupporting
confidence: 93%
“…NeuroBloc and the type A toxins had a similar anhidrotic effect, but the effect of NeuroBloc seemed to diminish more prominently at measurement week 12. This is in accordance with previous clinical studies (15,16). Moreover, the study confirms previous observations of NeuroBloc as an autonomic and sudomotor neurone-specific agent with comparatively poor effect on muscles (12,15,17).…”
Section: Discussionsupporting
confidence: 93%
“…A similar early effect of rimabotulinum toxin was observed in another small trial in patients with axillary hyperhidrosis (Frasson et al, 2011). Kranz et al (Kranz et al, 2011) compared intradermal injections of 4e8 MU onabotulinum toxin and 150e600 MU rimabotulinum toxin in 18 volunteers and measured the effect and time course of sweat secretion over 54 weeks. Both toxins significantly reduced sweating.…”
Section: Comparison Of Bont Type a Versus Type B In Motor And Autonomsupporting
confidence: 60%
“…In these studies the clinical equipotency ratio seemed to be quite different from that found for muscles. In a comparative study on healthy volunteers, the ability to induce anhidrosis was tested with Ona/A and B/Rima in a conversion ratio of 1:75 at different dilutions (Kranz et al, 2011). The results of this study are interesting: in that the peak effect was at week 3 for both toxins, with significantly larger anhidrotic areas for B/Rima.…”
Section: Clinical Equipotency Of Bont/a and Bont/b In Autonomic Disormentioning
confidence: 91%
“…Thereafter, the rate of decline was lower in A/Ona and after week 24, mean A/Ona areas were larger. They observed a gender-related difference in both products (less effective in women), and effect of dilution higher in B/Rima; finally they concluded that for dermatologic uses the proper A/Ona:B/Rima ratio is 1:29 (Kranz et al, 2011).…”
Section: Clinical Equipotency Of Bont/a and Bont/b In Autonomic Disormentioning
confidence: 96%